Exploring elements of human capital development of private hospitals in Malaysia: a qualitative approach / Hazlina Hassan ... [et al.] - Hassan, Hazlina; Mohd.Saleh, Norman; Kamaluddin, Amrizah; Hamzah, Noradiva (2017)
Human Capital Development (HCD) is one of the key pillars of the Malaysian Government's Economic Plans in its efforts to increase the technical skills, creativity and innovation required to drive Malaysia's knowledge based economy. The growth of talented human capital is essential towards organization's competitive advantage. HC as one of the components of Intellectual Capital becomes very important in service sector especially the healthcare industry. Many literatures show that HC has positive relationship with organization's performance. However, in healthcare sector, it can be questioned on how elements of HC are being measured and are there any indicators developed to standardize it. The purpose of the study is to explore whether people within top management of hospitals have similar opinions on the most important elements of HC that might be used to determine hospital's strategies. This study also seeks to investigate whether these HC elements really necessary and important in the creation of value for the hospital. This study employs qualitative approach and in-depth interview sessions also were carried out among the top tier hospitals in Malaysia. Cross-case study analysis was carried out in analysing the data collected. The findings reveal that there are five elements of HC which are very important in setting the hospital strategies; recruitment requirements, post basic skills availability, career pathway, employees capabilities and enhancement. The patterns found in this content analysis technique shows that HC in hospitals is highly influenced by clinical and non-clinical elements. Competencies of clinical staff is crucial in hospital. Presently, there is no common international framework in identifying, measuring and disclosing of information on HC that is available and widely used in Malaysian hospitals. Therefore, it is most appropriate to put effort in developing a standard measurement and management technique for hospitals in process to identify, measure, manage and value their HC assets.